FRI0376 DIFFERENCES IN PHYSICAL ACTIVITY BETWEEN AXIAL SPONDYLOARTHRITIS PATIENTS WITH AND WITHOUT PHYSICAL THERAPY. (June 2019) - Hilberdink, Bas; Giesen, Florus van der; Vlieland, Thea Vliet; van Gaalen, Floris A.; Ronday, Karel; Peeters, Andreas; Weely, Salima van
Abstract : Background: Physical activity (PA) according to public health guidelines is effective and safe for people with rheumatic and musculoskeletal diseases, including axial spondyloarthritis (axSpA), and should be promoted by healthcare providers. 1 In axSpA, in particular high intensity aerobic PA is beneficial, yet this was found to be incompletely implemented in physical therapy programs. 2 Studies describing aerobic PA in axSpA patients with and without physical therapy are lacking. Objectives: To describe the amount, frequency and intensity of aerobic PA in axSpA patients with and without physical therapy treatment. Methods: A survey, which included questions on patient characteristics, current physical therapy use (individual or group), PA (Short QUestionnaire to ASess Health-enhancing PA (SQUASH)) and health status (Assessment of Spondyloarthritis International Society Health Index (ASAS HI)), was sent by postal-mail to 458 axSpA patients registered in three hospitals in the Netherlands. From the SQUASH, besides amount (minutes/week) of all PA and meeting the PA guideline (≥30 minutes ≥moderate PA on ≥5 days/week; yes/no), also the amount and frequency (sessions/week) of moderate and vigorous intensity aerobic PA during commuting and leisure (including sports) were extracted. Differences in PA behaviour between patients with and without current physical therapy were analyzed with the Mann-Whitney U or Chi-square test, where appropriate. Results: The questionnaire was returned by 206 axSpA patients (response rate: 45%) of whom 200 completed the SQUASH correctly. Overall, 64% met the PA guideline. Half of the patients were using physical therapy (n=99; 77 individual, 11 group and 11 both); these patients had a significantly longer disease duration. Regarding overall PA, there were no differences in the total amount and the proportion meeting the guideline between patients with and without physical therapy. For moderate intensity aerobic PA, both the amount and frequency were significantly greater in the group with physical therapy, whereas for vigorous intensity aerobic PA there were no differences between the groups (Table 1 ). Conclusion: More than half of people with axSpA were physically active according to public health PA guidelines. People using physical therapy engaged in significantly more moderate intensity, but not high intensity aerobic PA than those without physical therapy. These results indicate that high intensity aerobic PA should be more intensively advocated and implemented, also in physical therapy treatment. References: [1] Rausch Osthoff, et al. Ann Rheum Dis. 2018;77:1251-1260. [2] Niedermann, et al. Arthritis Care Res. 2018. Doi:10.1002/acr.23705 Acknowledgement: This study was funded by the Dutch Arthritis Society. Disclosure of Interests: None declared